2009
DOI: 10.1021/la900919w
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Layers of Sodium Caseinate + Dextran Sulfate: Influence of Order of Addition to Oil−Water Interface

Abstract: We report on the interfacial properties of electrostatic complexes of protein (sodium caseinate) with a highly sulfated polysaccharide (dextran sulfate). Two routes were investigated for preparation of adsorbed layers at the n-tetradecane−water interface at pH = 6. Bilayers were made by the layer-by-layer deposition technique whereby polysaccharide was added to a previously established protein-stabilized interface. Mixed layers were made by the conventional one-step method in which soluble protein−polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 48 publications
7
75
0
Order By: Relevance
“…In fact the presence of substantial inter-diffusion in multi-layers, as well as lateral diffusion, has been reported by Yoo et al (2008). Other evidence for changes in the structure of multi-layers come from the work of Jourdain, Schmitt, Leser, Murray, & Dickinson (2009). In this study, interfacial adsorbed films were formed on n-tetradecane -water interfaces in two different ways, involving mixtures of sodium caseinate and dextran sulphate.…”
Section: Introductionsupporting
confidence: 63%
“…In fact the presence of substantial inter-diffusion in multi-layers, as well as lateral diffusion, has been reported by Yoo et al (2008). Other evidence for changes in the structure of multi-layers come from the work of Jourdain, Schmitt, Leser, Murray, & Dickinson (2009). In this study, interfacial adsorbed films were formed on n-tetradecane -water interfaces in two different ways, involving mixtures of sodium caseinate and dextran sulphate.…”
Section: Introductionsupporting
confidence: 63%
“…This is about an order of magnitude smaller than experimental data obtained usingpotentials measurements. 29,30,53,61 This situation is altered dramatically for non-uniformly charged polysaccharides, as 45 evident from the data presented in Figs. 11b to 11d.…”
Section: Electrostatic Potentialmentioning
confidence: 86%
“…food emulsions). In a series of interesting experiments, Jourdain et al 53 compared the dynamic interfacial tension behaviour of the 25 mixed films of the protein, sodium caseinate, and the polysaccharide, dextran sulphate, adsorbed at n-tetradecane-water interfaces in two different ways. In the first of these, the adsorption took place in a single step from a mixed solution of these two biopolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is to be any adsorption of LBG this would have to be in the form of a secondary layer adsorbed on top of the primary caseinate layer. Adsorption of polysaccharides to hydrophobic-hydrophilic interfaces in this manner has been investigated both experimentally (Guzey & McClements, 2006;Guzey & McClements, 2007;Jourdain, Schmitt, Leser, Murray, & Dickinson, 2009) and through numerical theoretical calculations (Ettelaie, Akinshina, & Dickinson, 2008;Ettelaie, Akinshina, & Maurer, 2012). These studies have shown the need for strong favorable interactions between protein and polysaccharides before the formation of a secondary adsorbed layer by the latter can commence.…”
Section: Introductionmentioning
confidence: 99%